Bogdan Rusinek - założyciel oraz dowódca konspiracyjnej organizacji młodzieżowej "Harcerstwo Polskie" działającej na terenie Drezdenka w latach 1950-1951 = Bogdan Rusinek - the founder and the leader of the underground youth scouting organization "Harcerstwo Polskie" in the years 1950-1951 - Bartkowiak, Przemysław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article portrays Bogdan Rusinek, who was born January 24 1930 in Chełmno by the Vistula River and who, along with the former ZHP members, founded an underground pro-independence organization called "Harcerstwo Polskie" in October or November 1950 on the terrain of Drezdenko. He was the leader of this organization up until 1951. On October 30 and 31, 1951 the arrests of the members of "Harcertwo Polskie" began.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia